Growth Response of Some Leguminous Plants to Peat Water from Central Kalimantan - Decenly Decenly (Pandawa Institute, 2023)
Legumes are cultivated plants that are widely used by the community. In central Kalimantan, especially in Palangka Raya city, the legume is planted by the community as a garden plant which is consumed daily. The condition of acidic peatlands in Central Kalimantan is a limiting factor for plant growth. This study aims to determine the effect of peat water from the Sabangau River in Central Kalimantan on the germination of legume plants. The study used 4 (four) types of plants such as Vigna radiata L, Vigna unguiculata L, Phaseolus vulgaris L, and Glycine max L using a Completely Randomized Design (CRD). The plant seeds were first soaked in peat water for 3 (three) hours, then transferred to a medium covered with cotton and watered using the same water. Observations were made from the first day to the seventh day. The results showed that 3 (three) types of plants such as Vigna radiata L, Vigna unguiculata L, and Phaseolus vulgaris L were able to grow using peat water as a medium, while soybeans could not germinate. The results show that out of these three types of plants, Vigna radiata L has a better growth rate than Vigna unguiculata L and Phaseolus vulgaris L. Statistical tests using ANOVA analysis showed no significant differences between the three types of plants that grow.